Effects of Chronic Ethanol Consumption and Ovariectomy on the Spontaneous Alveolar Bone Loss in Rats - Priscila Cunha Nascimento; Leonardo Oliveira Bittencourt; Soraya O. Pinto; Luana N. S. Santana; Renata Duarte Souza-Rodrigues; Armando L. Pereira-Neto; Cristiane S. F. Maia; Cassiano K. Rösing; Rafael Rodrigues Lima (International Journal of Dentistry)
Postmenopausal estrogen deficiency and ethanol (EtOH) abuse are known risk factors for different diseases including bone tissues. However, little is known about the synergic effects of EtOH abuse and estrogen deficiency on alveolar bone loss in women. The present study evaluated the effects of EtOH chronic exposure and ovariectomy on the alveolar bone loss in female rats. For this, 40 female Wistar rats were randomly divided into 4 groups: control, EtOH exposure, ovariectomy (OVX), and OVX plus EtOH exposure. Initially, half of the animals were ovariectomized at 75 days of age. After that, the groups received distilled water or EtOH 6.5 g/kg/day (20% w/v) for 55 days via gavage. Thereafter, animals were sacrificed and the mandibles were collected, dissected, and separated into hemimandibles. Alveolar bone loss was evaluated by measuring the distance between the cementoenamel junction and the alveolar bone crest through a stereomicroscope in 3 different anatomical regions of the tissue. One-way ANOVA and post hoc Tukey were used to compare groups (p<0.05). The results showed that the ovariectomy and EtOH exposure per se were able to induce alveolar bone loss, and their association did intensify significantly the effect. Therefore, OVX associated with heavy EtOH exposure increase the spontaneous alveolar bone loss in rats.